Obsuždenie «central'nych» i «perifericeskich» faktorov aerobnoj proizvoditel'nosti i realizacionnoj effektivnosti v kontekste special'noj rabotosposobnosti sportsmenov v vidach sporta na vynoslivost' (obzor literatury) - Myakinchenko, E. B.; Kryuchkov, A. S.; Missina, S. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Despite the long history of research, there are currently no comprehensive answers about the importance of "central" and/or "peripheral" factors of physical abilities for sports performance of high-class athletes in endurance sports. The reviewdiscusses the traditional views and modern ideas of supporters of both the "central" and the "peripheral" hypotheses. Specifically in the light of the fact that athletes have an uttermost arteriovenous oxygen difference in the main muscles (i.e., their high oxidative capacities), it is difficult to dispute the high and often the decisive role of the cardio-respiratory system capacities for VO2max. However, the fact of a low correlation of VO2max with the competitive speed prompts to look for other factors significantly affected sports performance. For example, the role of such "peripheral" components as the ability to the fine-tune blood flow redistribution towards the main muscles. However, there is a reason to believe that the ability of athletes to increase competitive speed is associated with the maximum morph?-functional specialization of the athlete`s neuromuscular apparatus in accordance with the biomechanics of movements and the mode of muscle activity in the main competitive exercise. This neuromuscular system feature can increase the "power effect" of muscle efforts, mechanical efficiency, and athlete`s economics.It is discussed that this factor could increase the "Realization Effectiveness", which is understood as the ability to realize the potential of the functional capacities of athletes in competitions with maximum effect, but not only as a "perfect technique".